Pelaksanaan Pendidikan Agama Islam di Universitas Asahan dan Koherensinya dengan Surat Keputusan Direktur Jenderal Pendidikan Tinggi No. 43/Dikti/Kep/2006 - Sri Hairani Pohan (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
This study aims to analyze the learning of Islamic Religious Education at the Faculty of Economics, Asahan University. The problems studied include objectives, materials, methods, lecturer qualifications, facilities, semester credit load and learning evaluation. The various components of the problem will be analyzed for relevance by the letter of the Director General of Higher Education No. 43/DIKTI/Kep/2006 concerning guidelines for the implementation of personality development courses. The research method used is qualitative, with the technique of guaranteeing the validity of the data carried out by diligence, triangulation and member checking. The results of the study show that at Asahan University (1) the objectives of Islamic Religious Education are generally relevant to the decree in question (2) The learning materials are broadly adapted to the letter, but there is no syllabus and lesson plans prepared by lecturers of Islamic Religious Education. . (3) the learning method used is the lecture, discussion and question and answer method. (4) The qualifications of lecturers of Religious Education, Faculty of Economics, Asahan University are not relevant to the decree (5) The facilities provided are adequate to support the success of lectures, and this is also relevant to the said decree (6) The number of credits in learning is not relevant to the letter The decision letter referred to (7) evaluation of courses refers to the Faculty regulations, which is carried out with the first three stages of quizzes, second, mid-semester and lastly the end-of-semester exam.